Feasibility of Oral Glucose Tolerance Test as a Diagnostic Tool for Diabetes Prevalence Study in a Rural Community - Somannavar2, Ramesh Araganji3, Jayaprakash Appajigol1*, Manjunath (Recent Research in Science and Technology, 2011)
Introduction Diabetes population is relentlessly increasing. This rise is substantially contributed by increasing prevalence in rural communities. We need to have prevalence studies in different communities to know the nature of the disease. For conducting diabetes prevalence studies, best test to rely upon is OGTT. This study was aimed to examine the feasibility of conducting OGTT in a rural community as a diagnostic tool in diabetes prevalence study. Methods Meeting village leaders, arranging community gatherings and involving village representatives in health awareness program were the preparatory methods used in the study. Study team was trained to carry out various procedures involved. Every alternate person according to the electoral list was identified and reminded about his turn by repeated community announcements and meeting personally. Brief history, anthropometries were taken and OGTT was performed with 75 gram glucose load. Results Ã‚Â Out of 341 participants invited, 326 consented and 318 completed the study. Eight participants did not turn up for second blood test but under went all other procedures. We conducted ten screening visits to complete the entire study procedures. The response rate for consenting and entering the study was 95.6% and that for completing the study was 93.2%. Out of 318 participants completed the study, 182 (57.2%) were females and 136 (42.7%) males. So total time spent for 10 screening visits was 70 hours. Total cost of the screening the village was 20,520 Indian rupees. Conclusion The present study suggests that collecting OGTTs in rural communities is feasible. Committed research team, proper heath education, active involvement of the community members and long term association before starting the screening procedures results in better response rates.